Traffic jam in the primitive streak: The role of defective mesoderm migration in birth defects. Issue 8 (13th August 2014) - Herion, Nils J.; Salbaum, J. Michael; Kappen, Claudia; Finnell, Richard H.; Mitchell, Laura E.
<x xml:space="preserve">Abstract</x> Gastrulation is the process in which the three germ layers are formed that contribute to the formation of all major tissues in the developing embryo. We here review mouse genetic models in which defective gastrulation leads to mesoderm insufficiencies in the embryo. Depending on severity of the abnormalities, the outcomes range from incompatible with embryonic survival to structural birth defects, such as heart defects, spina bifida, or caudal dysgenesis. The combined evidence from the mutant models supports the notion that these congenital anomalies can originate from perturbations of mesoderm specification, epithelial–mesenchymal transition, and mesodermal cell migration. Knowledge about the molecular pathways involved may help to improve strategies for the prevention of major structural birth defects. Birth Defects Research (Part A) 100:608–622, 2014. © 2014 Wiley Periodicals, Inc.